2019
DOI: 10.1096/fj.201802479r
|View full text |Cite
|
Sign up to set email alerts
|

PDH‐mediated metabolic flow is critical for skeletal muscle stem cell differentiation and myotube formation during regeneration in mice

Abstract: Skeletal muscle satellite cells (SMSCs), the major stem cells responsible for the regeneration of skeletal muscle, are normally cell cycle arrested but differentiate to generate myocytes upon muscle damage, forming new myofibers along with self‐renewing stem cells in preparation for subsequent injury. In this study, we investigated which factors stimulate the proliferation and differentiation of SMSCs and found that pyruvate, the end product of glycolysis, stimulates their differentiation. Pyruvate antagonizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…Pluripotent and some adult stem cells have devised this method to inhibit mitochondrial Oxphos and enhance glycolysis to sustain rapid proliferation (Folmes et al, 2011;Takubo et al, 2013). Although not much is known about regulation of MPCs by Pdk, it was shown that in hypoxia or glucose deprivation, MPCs have higher Pdk activity to support enhanced glycolysis (Abbot et al, 2005;Hori et al, 2019).…”
Section: Mitochondrial Oxphos and Satellite Cell Fatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pluripotent and some adult stem cells have devised this method to inhibit mitochondrial Oxphos and enhance glycolysis to sustain rapid proliferation (Folmes et al, 2011;Takubo et al, 2013). Although not much is known about regulation of MPCs by Pdk, it was shown that in hypoxia or glucose deprivation, MPCs have higher Pdk activity to support enhanced glycolysis (Abbot et al, 2005;Hori et al, 2019).…”
Section: Mitochondrial Oxphos and Satellite Cell Fatesmentioning
confidence: 99%
“…Despite this shortcoming the past few years have witnessed mitochondrial function linked to dictating SC fate determination, whether to maintain quiescence, become activated, self-renew or commit to differentiate. Importantly, mitochondrial energy output is associated with SC functional outcomes (Lyons et al, 2004;Folmes et al, 2012;Ryall et al, 2015b;Hori et al, 2019). Besides harvesting energy, mitochondria also have other essential functions linked to SC fate decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations by many laboratories over the past several decades emphasized the integral role of the mitochondrial pyruvate dehydrogenase complex (PDC) in regulating fuel metabolism and organismal homeostasis in health and during both physiologic and pathologic stress . Under aerobic conditions, PDC catalyzes the rate‐determining step in aerobic glucose oxidation by irreversibly decarboxylating glycolytically derived pyruvate to acetyl coenzyme A (acetyl‐CoA), which condenses with oxaloacetate to form citrate in the tricarboxylic acid (TCA) cycle.…”
Section: Introductionmentioning
confidence: 99%
“…PDH-regulated flux of pyruvate into the TCA cycle has been shown to be critical for MuSC differentiation and tissue regeneration 28 . Defective MuSC mitochondrial function results in impaired tissue regeneration 29 and MuSCs with greater mitochondrial content and oxidative phosphorylation are associated with increased capability of initiating myogenic colonies 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, numerous studies have identified a positive correlation between MuSC oxidative capacity and several aspects of MuSC function including cell number and muscle regenerative activity [22][23][24] . Several recent reports have delineated mechanisms that connect key tricarboxylic acid (TCA) cycle intermediates with transcriptional and epigenetic changes important for the function of MuSCs in muscle regeneration [25][26][27][28][29] . Indeed, cellular metabolism has been linked to quiescence, self-renewal, and differentiation function in other tissue-specific stem cell systems as well [30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%